Myanmar Human Capital Development, Employment, and Labor Markets - Sakiko Tanaka; Christopher Spohr; Sandra D'Amico (Asian Development Bank (ADB), 2015)
Improvement in human capital is essential for rapid, sustainable, and inclusive economic growth in Myanmar. Investments in health and education - including technical and vocational education and training - are essential to engineer a productive labor force that can contribute to and benefit from growth opportunities, while equipping the country's young population to participate in the country's dramatic socioeconomic transformation. This paper focuses on developing human capital, with an emphasis on health and education in the context of employment growth and an employment-enabling environment. While awaiting the release of up-to-date data and the outcome of broad ongoing legislative reforms, the paper draws on extensive analysis of available data, including the Integrated Household Living Condition Survey 2009-2010, nationally led assessments, and consultations with the government and a variety of stakeholders to provide a snapshot of important recent developments that are helping to shape the transformation.
hdl:11540/5303
Keywords: E24; I15; I25; O15; 330; education; employment; health; Myanmar; technical and vocational education and training (TVET)